Religious Minorities in Iran - Nazila Ghana-Hercock (International Institute of Islamic Thought, 2000)
The author is an associate professor of political science at the University of Southern California. Her previous publications include a 1982 Praeger publication, "The Women's Rights Movement in Iran: Mutiny, Appeasement, and Repression from I 900 co Khomeini." Religious Minorities in Iran is of interest to political scientists, particularly those focused on the Middle East; Iran experts; Islamic studies experts concerned with modem-day politics and governance; those in the field of religious studies or comparative religion; and also lawyers, academics, and those working in Non-Governmental Organizations (NGOs) in the human rights field who are interested in issues related to minority rights, freedom of religion or belief, and human rights in the Middle East. The book focuses on those identified as the main ethnoreligious components of the non-Muslim religious communities in Iran: Armenians, Assyrians, Chaldeans, Jews, Zorascrians, Baha'fs, and Iranian Christian converts. The main period of study is the first decade of the Islamic Revolution of Iran, 1979 to 1989. The author gives three reasons for focusing on this period; she argues that this was the most ideologically charged moment of the revolution, that the position of recognized non-Muslim minorities was largely routinized by the late 1980s, and because she wants to avoid the nuances that emerge and complicate the political scene after the end of the cold war and the formation of post-Soviet states. Later periods are mainly considered only when they bear direct relevance to the points being made and in the concluding chapter ...